Effect of nutrient concentration and growing seasons on growth, yield and quality of leafy lettuce (Lactuca sativa L.) in a hydroponic system - Soundy, Puffy (University of Pretoria, 2013)
Dissertation (MInstAgrar)--University of Pretoria, 2012.